Peer Effects in Prison - Julian V. Johnsen; Laura Khoury (Institute of Labor Economics (IZA), 2024)
Peer interactions play a key role in the criminal sector due to its secrecy and lack of formal institutions. A significant part of criminal peer exposure happens in prison, directly influenced by policymakers. This paper provides a broader understanding of how peer effects shape criminal behavior among prison inmates, focusing on co-inmate impacts on recidivism and criminal network formation. Using Norwegian register data on over 140,000 prison spells, we causally identify peer effects through within-prison variation in peers over time. Our analysis reveals several new insights. First, exposure to more experienced co-inmates increases recidivism. Second, exposure to "top criminals" (i.e. those with extreme levels of criminal experience) plays a distinctive role in shaping these recidivism patterns. Third, inmates form lasting criminal networks, as proxied by post-incarceration co-offending. Fourth, homophily intensifies these peer effects. These findings contribute to the theoretical understanding of peer influences in criminal activities and offer practical insights for reducing recidivism through strategic inmate grouping and prison management policies.
Keywords: K14; K42; 330; prison inmates; incarceration; criminal behavior; criminal experi- ence; criminal networks; recidivism